Hakikat Penyucian Jiwa (Tazkiyat An-Nafs) dalam Perspektif Al-Ghazali - Lita Fauzi Hanafani; Radea Yuli A Hambali (Gunung Djati Conference Series, 2023)
This study aims to discuss the nature of purification of the soul (tazkiyat an-nafs) from Al-Ghazali's perspective. The research method used is a qualitative type through literature study. The results and discussion of this study are that there are two natures of soul purification according to Al-Ghazali, namely: first, cleansing the soul of all reprehensible qualities which in essence is to get rid of all liver disease. Second, decorate the soul with various praiseworthy qualities that are blessed by Allah swt. This study concludes that Al-Ghazali is one of the philosophers who discusses tazkiyatun nafs. tazkiyatun nafs according to Al-Ghazali is a process to cleanse the human soul from various impurities both externally and spiritually. As disclosed by Jaelani who quoted him in the book Bidayatul Hidayah that Al-Ghazali has defined that tazkiyatun nafs is an effort to purify oneself from self-praise. For the essence of soul purification according to Al-Ghazali there are two, namely: first, cleansing the soul of all reprehensible qualities, which in essence is to get rid of all heart ailments. secondly decorate the soul with various commendable qualities that are blessed by Allah swt. To achieve this, it is necessary to have a method including 1 takhalli, 2. Tahalli and 3. Tajalli.